CINEMA EXPANDIDO PORTUGUÊS DO SÉC. XXI - Prof. Doutor Paulo CUNHA (Fonseca, Journal of Communication, 2023)
It would be very interesting case studies for various reflections on various issues, but we chose to know in more detail the path of three young Portuguese artists who have put dialogue between film language and contemporary art, exploring the multiple relationships between the cinema and the art gallery. Because of the international projection of his work and the complexity of his work, but also the easier access to his works, I chose to look into the cases of Gabriel Abrantes, Filipa César and Salomé Lamas, knowing that many other aspects would be, in a way, placed in parallel or secondary plane.